Challenges for Developers Implementing IBS in Malaysian Housing Projects - Abd Jalil, Ahmad; Nuruddin, Azlan Raofuddin; Jaafar, Mastura; Othuman Mydin, Md Azree (2015)
Housing projects has become one of the contributors to Malaysian construction industry and there is always significant demand for housing as Malaysian economic has spurs positively. However, reports from National Housing Policy (2012) has revealed that current housing projects must transform from issues of low quality, delay, lack of skilled labour and slow adaptation of technology. Therefore the government has enforced prefabrication concept to be implemented in Malaysian housing sector to overcome these issues. Housing should be the sector that most suitable implementing IBS due to its construction nature where repetitious drawings and similar layout and specification are used for every unit. Recent study shows that IBS adoption in housing projects still behind the target. There are many challenges that discourage housing developers to adopt this prefabrication technology. This paper aims to discuss the challenges that housing developer encounter which discourage them from implementing IBS and at the end of this paper, some suggestions to overcome the challenges are proposed. This paper is based on previous research, journals and government reports as evidence. It can be concluded that Malaysian housing market still facing many barriers on IBS and needs a radical transformation that requires much more effort particularly on procurement system, supply chain and skill workers. In order to sustain the IBS usage, all parties must put great attention where this technology becomes priority, and not only as an alternative method.